La Place du Surtitrage Comme Mode de Traduction et Vecteur D’échange Culturel pour les Arts de la Scéne - Dewolf, Linda (Theatre Research in Canada / Recherches théâtrales au Canada, 2003)
Despite the fact that surtitling is a rapidly expanding field which enables plays and operas to be understood by audiences in different countries unfamiliar with the original language, this research area is quite new and relatively unexplored. The question of how the actual verbal and non-verbal material is structured in surtitling has received only minimal analysis in scholarly terms so far. Very little has been written on the reasons for reduction methods. Up to now scholars seem not to have considered the new context which surtitling offers for an intertextual approach to translations. This study starts from the idea that surtitling is a translation constrained by its context, by time and space as much as by culture and the multi-semiotic levels of the performance. Opera, puppet theatre and drama are not only made of text; they involve visual and musical signs which may be looked at in a new light, from an inter-artistic semiotic perspective. Surtitling enables cultural exchanges; further investigation of its role as such is not only needed, but makes it one of several interesting new fields of research in translation and intercultural studies.